Fifteen from one: a revision of the Galaxias olidus Günther, 1866 complex (Teleostei, Galaxiidae) in south-eastern Australia recognises three previously described taxa and describes 12 new species - Raadik, Tarmo A. (Zootaxa, 2014)
The systematics of the Galaxias olidus hyper-species complex from freshwater habitats in south-eastern, mainland Australia is revised. Galaxias olidus Günther 1866 is redescribed, Galaxias fuscus Mack 1936 and Galaxias ornatus Castelnau 1873, previously synonymised with G. olidus (sensu lato), are reinstated as valid taxa and redescribed, and 12 taxa are described as new: Galaxias aequipinnis sp. nov., Galaxias arcanus sp. nov., Galaxias brevissimus sp. nov., Galaxias gunaikurnai sp. nov., Galaxias lanceolatus sp. nov., Galaxias longifundus sp. nov., Galaxias mcdowalli sp. nov., Galaxias mungadhan sp. nov., Galaxias oliros sp. nov., Galaxias supremus sp. nov., Galaxias tantangara sp. nov., and Galaxias terenasus sp. nov. These species are morphologically similar and, whilst there is extensive overlap in meristic counts and morphometric characters, each can be diagnosed by unique combinations of characters, including allozyme loci and colour pattern; morphological diagnosis is improved greatly if based on freshly formalin-fixed material. Galaxias schomburgkii Peters 1868, Galaxias bongbong Macleay 1881, Galaxias kayi Ramsay & Ogilby 1886 and Galaxias oconnori Ogilby 1912 are retained as junior synonyms of G. olidus (sensu stricto). The types for Galaxias findlayi Macleay 1882 are lost and no specimens matching its description were collected or examined from the Mt. Kosciuszko region; it is also currently retained as a junior synonym of Galaxias olidus s.s. The species G. terenasus sp. nov. and G. arcanus sp. nov. are the most morphologically specialised in the complex and G. olidus s.s remains the most morphologically variable species. It also remains the most widespread taxon, though its previously known distribution is reduced, particularly in the south-west of its range. Nine species are narrow-range endemics, known from one, or only a few, locations, and these restricted distributions most probably reflect the fragmentation and reduction of former ranges caused by the effects of alien salmonids. Eleven species are of conservation concern, most are considered critically endangered.